A Nursing Survey on Nutritional Care Practices in French-Speaking Pediatric Intensive Care Units: NutriRéa-Ped 2014. Issue 1 (January 2016) - Valla, Frédéric V.; Gaillard-Le Roux, Bénédicte; Ford-Chessel, Carole; De Monte, Malorie; Tume, Lyvonne; Letois, Flavie; Mura, Thibault; Choueiry, Elie; Rooze, Shancy; Moullet, Clémence; Jotterand-Chaparro, Corinne; Jacquot, Aurélien
ABSTRACT: Objectives: Malnutrition in critically ill children contributes to morbidity and mortality. The French-speaking pediatric intensive care nutrition group (NutriSIP) aims to promote optimal nutrition through education and research. Methods: The NutriSIP-designed NutriRéa-Ped study included a cross-sectional survey. This 62-item survey was sent to the nursing teams of all of the French-speaking pediatric intensive care units (PICUs) to evaluate nurses' nutrition knowledge and practices. One nurse per PICU was asked to answer and describe the practices of their team. Results: Of 44 PICUs, 40 responded in Algeria, Belgium, Canada, France, Lebanon, Luxemburg, and Switzerland. The majority considered nutrition as a priority care but only 12 of the 40 (30%) had a nutrition support team, 26 of the 40 (65%) had written nutrition protocols, and 19 of 39 (49%) nursing teams felt confident with the nutrition goals. Nursing staff generally did not know how to determine nutritional requirements or to interpret malnutrition indices. They were also unaware of reduced preoperative fasting times and fast-track concepts. In 17 of 35 (49%) PICUs, the target start time for enteral feeding was within the first 24 hours; however, frequent interruptions occurred because of neuromuscular blockade, fasting for extubation or surgery, and high gastric residual volumes. Combined pediatric neonatal intensive care units were less likely to perform systematic nutritional assessment and to start enteral nutrition rapidly. Conclusions: We found a large variation in nursing practices around nutrition, exacerbated by the lack of nutritional guidelines but also because of the inadequate nursing knowledge around nutritional factors. These findings encourage the NutriSIP to improve nutrition through focused education programs and research. Abstract : Supplemental Digital Content is available in the text